2022
DOI: 10.1155/2022/1569960
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Potential of Harvested Wood Fuel by Refugees in Northern Uganda

Abstract: For the last three decades, Uganda has lost considerable natural vegetation cover in the refugee settlements and buffer zones due to the high demand for wood fuel and timber. It is worthy to note that the supplies of wood fuel are more likely to dwindle in the near future. This study explored the determinants of harvested wood-fuel choices and their energy potential. It also examined the implemented energy conservation measures and constraints faced by the refugees both in Palorinya and Imvepi refugee settleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A majority of community members collecting rewood belong to the middleaged group (40 to 44 years), have no formal education, and have a big family size (average 6 members). The difference in frequency of rewood collection between difference household size may be contributed by the need to provide more food for bigger household size as found by Barasa et al (2022) in Uganda. The biggest difference can be seen between the larger and smaller household sizes.…”
Section: Socio-demographic Factors In Uencing the Frequency Of Ntfps ...mentioning
confidence: 99%
“…A majority of community members collecting rewood belong to the middleaged group (40 to 44 years), have no formal education, and have a big family size (average 6 members). The difference in frequency of rewood collection between difference household size may be contributed by the need to provide more food for bigger household size as found by Barasa et al (2022) in Uganda. The biggest difference can be seen between the larger and smaller household sizes.…”
Section: Socio-demographic Factors In Uencing the Frequency Of Ntfps ...mentioning
confidence: 99%
“…Times in the high-speed development, rapid socio-economic development, and economic and social prosperity behind a prosperous scene are all kinds of uncontrolled exploitation and depletion of resources, more and more land on the construction of skyscrapers and roads and bridges to adapt to the development of mankind [1][2]. Therefore, the environment is polluted and destroyed, resources are depleted, and there is a serious ecological imbalance [3]. In recent years, the state has increased its attention towards the construction of ecological civilization, and people's awareness of ecological and environmental protection is increasing day by day.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, S studied the ecological landscape of Dongting Lake wetland and found that the restored wetland was able to maintain a large waterbird capacity and diversified waterbird populations in winter, and the restoration of the wetland flora and fauna also laterally reflected the sensitivity of the wetland ecosystems to the environmental changes [17]. Zhong, Y et al applied species distribution models (SDMs) to wetland restoration, and they found that the potential wetland restoration area was 1.51× 3 10 2 km and 1.48× 3 10 2 km under RCP4.5 and RCP8.5 scenarios, respectively [18].…”
Section: Introductionmentioning
confidence: 99%